2020
DOI: 10.4067/s0718-381x2020000400685
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Vital Signs and Laboratory Tests in Patients with Odontogenic Infections Requiring Hospitalization

Abstract: The purpose of this study was to evaluate the changes in vital signs and laboratory tests of patients with odontogenic infections who required hospitalization as well as checking their effectiveness in determining the severity of the case and possible correlations with the length of stay. Patients with odontogenic infections who required hospitalization were assessed prospectively between October 2016 and April 2018. The patients were divided into two groups considered as simple (Group 1) or complex (Group 2) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 25 publications
0
3
0
1
Order By: Relevance
“…Pavan et al [ 18 ] implemented a prospective research of 50 cases diagnosed with OI. They aimed to detect the value of vital sign changes and laboratory tests in determining the severity and length of stay (LOS).…”
Section: Resultsmentioning
confidence: 99%
“…Pavan et al [ 18 ] implemented a prospective research of 50 cases diagnosed with OI. They aimed to detect the value of vital sign changes and laboratory tests in determining the severity and length of stay (LOS).…”
Section: Resultsmentioning
confidence: 99%
“…Weyh, et al Published a guideline for CT request that considers signs and symptoms as "red flags" that impart an increased risk Of dissemination of the infection to deep anatomic spaces thus increasing the risk of complications 20 but on other hand Computed Tomography (CT) and laboratory tests such as white blood count and C-Reactive Protein (CRP) are of great importance to the professional because they can help to identify severity and guide treatment. 4,21 Because of its good sensitivity to characterize soft tissues (varying between 60%-100%), contrast-enhanced cervical CT is often used as the standard method to assess the extent of deep neck space infections. 22 Assess to Ultrasonography is easily and free of ionizing radiation, but it is less sensitive for deeper cervical tissues.…”
Section: Discussionmentioning
confidence: 99%
“…Studies found that more severe odontogenic infections were present in the patuents who were smokers or drug abusers. [3][4][5] The aim of this study is to review the clinical characteristics and management of submandibular space infections.…”
Section: Introductionmentioning
confidence: 99%
“…Hospitalizációt igénylő odontogén gyulladások esetén a felvétellel egy időben, 24 órával később, majd 48 óránként javasolt laborkontrollt végezni, amelyből kiemelendő a balra tolt vérkép és a gyulladásos paraméterek emelkedésével szoros korrelációt mutató hospitalizációs idő [25].…”
Section: Laborvizsgálatunclassified